#### Provide solution for RD Sharma maths class 12 chapter Higher Order Derivatives exercise 11.1 question 34

Proved

Hint:

You must know the derivative of exponential and cos inverse function

Given:

$y=e^{a \cos ^{-1} x} , \text { prove }\left(1-x^{2}\right) \frac{d^{2} y}{d x^{2}}-x \frac{d y}{d x}-a^{2} y=0$

Solution:

$y=e^{a \cos ^{-1} x}$

\begin{aligned} &\text { Taking logarithm both sides }\\ &\log y=a \cos ^{-1} x \log c\\ &\log y=a \cos ^{-1} x\\ &\frac{1}{y} \frac{d y}{d x}=a \times\left(\frac{-1}{\sqrt{1-x^{2}}}\right)\\ &\frac{d y}{d x}=\frac{a y}{\sqrt{1-x^{2}}} \end{aligned}

\begin{aligned} &\text { Squaring both sides, }\\ &\left(\frac{d y}{d x}\right)^{2}=\frac{a^{2} y^{2}}{\left(1-x^{2}\right)}\\ &\left(1-x^{2}\right)\left(\frac{d y}{d x}\right)^{2}=a^{2} y^{2} \end{aligned}

\begin{aligned} &\text { Again differentiate, }\\ &\left(\frac{d y}{d x}\right)^{2}(-2 x)+\left(1-x^{2}\right) \times 2 \frac{d y}{d x} \frac{d^{2} y}{d x^{2}}=a^{2} \cdot 2 y \cdot \frac{d y}{d x}\\ &-x \frac{d y}{d x}+\left(1-x^{2}\right) \frac{d^{2} y}{d x^{2}}=a^{2} y\\ &\left(1-x^{2}\right) \frac{d^{2} y}{d x^{2}}-x \frac{d y}{d x}-a^{2} y=0 \end{aligned}